2012
DOI: 10.3346/jkms.2012.27.3.255
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Using the EuroQol 5D Questionnaire in Korean Patients with Type 2 Diabetes

Abstract: We aimed; 1) to determine the validity of the EuroQol 5D (EQ-5D) for the health-related quality of life (HRQOL) of Korean patients with type 2 diabetes, and 2) to identify associated factors of the HRQOL of these patients. Follow-up surveys were conducted for consecutive patients with type 2 diabetes. HRQOL was assessed using the EQ-5D and the Short Form-36 (SF-36). The validity of EQ-5D was assessed with the perspectives of known group, convergent and discriminant validity. Additionally, a linear mixed model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
98
6
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(127 citation statements)
references
References 13 publications
21
98
6
2
Order By: Relevance
“…We measured the health status by EQ-5D and calculated the EQ-5D score, to investigate the relationship between EQ-5D and VAS scores and patient characteristics that are associated with HRQoL. Synthesis of literature indicated that the EQ-5D has been used to measure HRQoL of diabetic patients in different countries [15][16][17][18][19]. The EQ-5D has been used in the UK Prospective Diabetes Study (UKPDS) to determine the effects of therapy, complications, and hypoglycemic episodes on HRQoL in patients with T2DM too [20].…”
Section: Discussionmentioning
confidence: 99%
“…We measured the health status by EQ-5D and calculated the EQ-5D score, to investigate the relationship between EQ-5D and VAS scores and patient characteristics that are associated with HRQoL. Synthesis of literature indicated that the EQ-5D has been used to measure HRQoL of diabetic patients in different countries [15][16][17][18][19]. The EQ-5D has been used in the UK Prospective Diabetes Study (UKPDS) to determine the effects of therapy, complications, and hypoglycemic episodes on HRQoL in patients with T2DM too [20].…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to the fact that the respondents in our study thought that they were healthy and have no health problems as monks are generally driven by religious and spiritual beliefs and healing system than the rest of the population. Out of all the HRQoL tools, we chose to use EQ-5D-5L in our study among diabetic monks since It is simple to use, provides sufficient responsiveness to changes in health states and relatively wide range of utility scores generated by this tool 9,[19][20][21] . In our study among diabetic monks, it was seen that the mean score of EQ-5D-5L was seen to be comparatively better than that of EQ-VAS with 0.89 and 0.71, respectively which means that 89.5% good health was reported by EQ-5D-5L, which is in accordance to a study among diabetic patients 10,22 .…”
Section: Discussionmentioning
confidence: 99%
“…In the domain of anxiety/depression in a study in Korea [36], patients in the elementary school or below group had lower EQ-5D index scores than those in the middle/high school and university or above groups. People with longer duration of education reported statistically significant higher mean score in the field of mental health in a study in Greece [31], while in a study in Nigeria [29] there was no significant correlation between quality of life and level of education.…”
Section: Discussionmentioning
confidence: 93%